Biometric Based Attendance Management System using Cloud - Jagadish S Kallimani, Monish Narendra, Veena G S, Divakar Harekal (International Journal of Advanced Science and Technology, 2020)
Biometrics is the technical term for body measurements and calculations. Biometric technology refers to identification and verification of individuals by analyzing the human body characteristics. In modern times, there has been high level of identity theft experienced on a day to day basis. Companies, Organizations and Institutions are generally concerned over the levels of employee absence in the workplace, where security is essential, access to restricted areas are controlled and monitored through a system. Most institutions find it hard to managing student’s attendance during lecture periods. Manually taking attendance by hand and preserving it over a long period adds to the difficulty and wastes a lot of time. For these reasons an effective system is proposed in this paper to solve the problem of manual attendance. Here a system would take attendance electronically with the help of a fingerprint recognition system and all records are saved in cloud or locally in the device. A staff biometric attendance would contain a system to calculate attendance of the staff and do further calculations such as monthly attendance summary and calculate wages based on attendance, etc. In addition, this system if implemented properly could increase productivity, can reduce truancy, lateness in organization and institution.